Clinical aspects and relevance of molecular diagnosis in late mucocutaneous leishmaniasis patients in Paraná, Brazil - Andréa Thomaz-Soccol; Marcos Mocellin; Fabiane Mulinari; Edilene Alcântara de Castro; Flávio de Queiroz-Telles; Fernanda de Souza Alcântara; Marcello Tortelli Bavaresco; Luciane Hennig; Anielo Andraus; Ennio Luz; Vanete Thomaz-Soccol (Brazilian Archives of Biology and Technology, 2011)
The aim of the present work was to study the clinical aspects and relevance of molecular diagnosis in late mucocutaneous leishmaniasis patients in Parana, Brazil. Twenty one suspected cases of mucocutaneous leishmaniasis (MCL) in patients from the endemic areas of leishmaniasis were assessed. Different methods used in diagnosing the disease and the polymerase chain reaction (PCR) technique were compared in order to establish the sensitivity of each method. Out of the 21 patients analyzed, 14.3% presented other etiologies such as vasculitis, syphilis, and paracoccidioidomycosis, with all tests negative for leishmaniasis. Out of the remaining 15 patients, 6.7% cases were confirmed for leishmaniasis by direct examination; 46.67% were positive for culture, which allowed isolating and identifying the parasite and - with the PCR technique - it was possible to diagnose 100% MCL patients for all the three repetitions of exams. The PCR optimized for the present work proved to be an auxiliary method for diagnosing leishmaniasis applicable in the patients carrying MCL due to Leishmania (Viannia) braziliensis and did not need culture to be performed, resulting in a faster diagnosis.